Strategi Bertahan di Era Persaingan yang Ketat Pedagang Angkringan di Daerah Semarang - Vio Argiansyah; Fatechatul Vitriyah; Rauly Sijabat (INDO PUBLISHING, 2026)
This study analyzes the survival strategies of street food vendors in the era of intense competition in Semarang. This research uses a qualitative phenomenological approach, with data analysis using thematic analysis methods based on Miles and Huberman. It can be concluded that the sustainability of street food vendors is inseparable from the ability of business owners to utilize existing resources and adapt to the dynamics of the business environment. This study shows that choosing a strategic location is a key factor in maintaining a business's existence, particularly for street food vendors located in educational areas. The location in front of the PGRI Semarang University campus provides a relatively stable flow of customers, especially among students, thus supporting the business's long-term sustainability. This confirms that location decisions are not merely technical factors but part of a competitive strategy that determines the competitiveness of street